THE EFFECT OF VITAMIN E (α-TOCOPHEROL) ADMINISTRATION ON GLOMERULUS AND PROXIMAL KIDNEY TUBULES DAMAGE WHICH RECEIVED CISPLATIN EXPOSURE ON SPRAGUE DAWLEY MICE - Rakhmatiar, Fadhilla; Soebadi, Doddy M.; Soetojo, Soetojo (Indonesian Urological Association, 2020)
Objective: To analyze the protective effect of Vitamin E on cisplatin toxicity in Sprague Dawley mice nephrons. Material & Methods: This is an experimental study using post-test only control group design, the subject was white male mice (Rattus Norvegicus) adult Sprague Dawley strain (10-12 weeks) of 24 rats divided into four groups. Negative control group (CN) got normal saline 0.9% intraperitoneal 1 cc, Positive control group (CP) got cisplatin 5 mg/kgBB, group P1 got vitamin E 50 mg/kgBB and Cisplatin 5 mg/kgBB, and P2 group got vitamin E 200 mg/kgBB plus cisplatin 5 mg/kgBB intraperitoneal. Cisplatin is conducted in the third week in each treatment group through intraperitoneal injection. Vitamin E is administrated per sonde for the first three weeks resumed on the fourth week to the seventh week. At the end of the seventh week, nephrectomy was performed on the treatment group to analyze the kidney damage. Histopathological observation is performed using a light microscope with a magnification of one hundred and four hundred times magnification. Results: Cisplatin administration resulted in significant tubular and glomerular damage compared to the control group. Increasing the dose of vitamin E in mice that received cisplatin resulted in significant nephron damage compared to the group who received cisplatin alone. Conclusion: Cisplatin administration results in nephrotoxicity in mice. The administration of high dose Vitamin E resulted in increased nephrotoxicity in mice that received cisplatin.